2021
DOI: 10.1016/j.scitotenv.2020.143346
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic danger to the deep: The risk of marine mammals contracting SARS-CoV-2 from wastewater

Abstract: We are in unprecedented times with the ongoing COVID-19 pandemic. The pandemic has impacted public health, the economy and our society on a global scale. In addition, the impacts of COVID-19 permeate into our environment and wildlife as well. Here, we discuss the essential role of wastewater treatment and management during these times. A consequence of poor wastewater management is the discharge of untreated wastewater carrying infectious SARS-CoV-2 into natural water systems that are home to marine mammals. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 35 publications
3
41
0
3
Order By: Relevance
“…We read with great interest the work by Mathavarajah et al (2020) “Pandemic danger to the deep: The risk of marine mammals contracting SARS-CoV-2 from wastewater,” (doi: https://doi.org/10.1016/j.scitotenv.2020.143346 ). We appreciate the novelty of the work and the focus on marine mammal protection from SARS-CoV-2 transmission via wastewater, but we would like to take the opportunity to highlight new relevant research and contextualize some of the discussion in the article.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the work by Mathavarajah et al (2020) “Pandemic danger to the deep: The risk of marine mammals contracting SARS-CoV-2 from wastewater,” (doi: https://doi.org/10.1016/j.scitotenv.2020.143346 ). We appreciate the novelty of the work and the focus on marine mammal protection from SARS-CoV-2 transmission via wastewater, but we would like to take the opportunity to highlight new relevant research and contextualize some of the discussion in the article.…”
mentioning
confidence: 99%
“… Bivins et al (2020) reported a 90% reduction in viable SARS-CoV-2 concentrations in 1.5 days in wastewater at room temperature and demonstrated that SARS-CoV-2 RNA was significantly more persistent than infectious virus. This work was not available at the time of publication of Mathavarajah et al (2020) . We agree with the authors that more research on survival of infectious SARS-CoV-2 in wastewater is needed to better interpret risk in various environments.…”
mentioning
confidence: 99%
“…Although this might not sound too alarming, there is still the potential for marine mammals to be in contact with the virus near sewage outlets. Recently, the issue of the susceptibility of marine mammals to SARS-CoV-2 has been further explored [ 96 ]. Here, the ACE2 receptor was once again used as a predictor of virus susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…What threat this may pose to aquatic life and those animals residing close to contaminated water has yet to be determined. Using an ACE2 receptor modeling approach, marine mammal susceptibility to infection has been evaluated, and fifteen species of seals, whales, and dolphins were identified as potentially vulnerable [ 88 ]. There is currently no data to support the presence of the virus in mammals exposed to wastewater contamination.…”
Section: Areas For Further Investigationmentioning
confidence: 99%